Grafting of Heparin on Blend Membrane of Citric Acid Crosslinked Chitosan/Polyethylene Glycol-Poly Vinyl Alcohol (PVA-PEG) - Retno Ariadi Lusiana; Ginanjar Argo Pambudi; Fitra Nilla Sari; Didik Setiyo Widodo; Khabibi Khabibi; Sri Isdadiyanto (Universitas Gadjah Mada, 2019)
Heparin, an active sulfate group material, grafted onto blend membrane citric acid cross-linked chitosan/poly (vinyl alcohol)-poly(ethylene glycol) (PVA-PEG) to improve the membrane properties. The physical tests shown that grafting reaction of citric acid crosslinked chitosan increased the mechanical strength and membrane swelling. The permeability test results, it was found that the grafted chitosan membrane was improved permeability of both urea and creatinine as compared to chitosan pure and chitosan crosslinked membrane. The negative charge of the sulphonate group of heparin increased the number of the active side of the carrier in the membrane, which then correlated to the membrane’s permeability process.